2008
DOI: 10.1590/s0101-20612008000300002
|View full text |Cite
|
Sign up to set email alerts
|

Desenvolvimento de embutido fermentado por Lactobacillus probióticos: características de qualidade

Abstract: A crescente preocupação dos consumidores em conhecer as características dos alimentos que consomem tem conduzido ao desenvolvimento de produtos que promovem a saúde e o bemestar, além de sua função de nutrição (TYÖPPÖNEN; PETÄJÄ; MATTILA-SANDHOLM, 2003). Esses alimentos que geram efeitos benéficos à saúde humana, aliados à ação nutricional são denominados funcionais. Seu efeito deve-se à adição de ingredientes ativos à remoção ou substituição de substâncias indesejáveis em sua composição (ERKKILÄ et al., 2001b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
11

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 18 publications
2
15
0
11
Order By: Relevance
“…since pH values below 5.7 adversely affect the development of this microorganism (STAHNKE, 1995). Papamanoli et al (2003) and Macedo et al (2008) working with fermented meats, also observed a drop in pH, and related this to the high number of probiotic Lactobacillus cells.…”
Section: Staphylococcus Sp Countmentioning
confidence: 93%
See 2 more Smart Citations
“…since pH values below 5.7 adversely affect the development of this microorganism (STAHNKE, 1995). Papamanoli et al (2003) and Macedo et al (2008) working with fermented meats, also observed a drop in pH, and related this to the high number of probiotic Lactobacillus cells.…”
Section: Staphylococcus Sp Countmentioning
confidence: 93%
“…Gravimetric methods were used to evaluate the moisture content (IAL, 2008), and weight loss, by weighing a piece of sausage (MACEDO et al, 2008).…”
Section: Physicochemical Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…The changes in the following physicochemical characteristics of sausages during the fermentation/maturation were determined as follows: (i) AW measured using the Aqualab CX2 (Decagon Devices Inc., Pullman, USA) (Ambrosiadis et al, 2004), (ii) pH measured using a digital potentiometer (Requipal RQ 210; Curitiba, Brazil) (Samelis et al, 1994), and (iii) weight loss estimated by a gravimetric method (Gehaka, São Paulo, Brazil) by measuring the difference between the initial weight and the final weight of the sausage pieces (Macedo et al, 2008).…”
Section: Monitoring Sausage Productionmentioning
confidence: 99%
“…Several studies have demonstrated starter culture viability in fermented sausages, such as Pediococcus pentosaceus and Staphylococcus xylosus (Coloretti et al, 2014), L. sakei and S. equorum (Simion et al, 2014), Lactobacillus gasseri (Arihara et al, 1998) Lactobacillus paracasei, Lactobacillus casei and Lactobacillus rhamnosus (Macedo, Pflanzer, Terra, & Freitas, 2008). …”
Section: Enterococcus Faecium Viability During Ripening Processmentioning
confidence: 99%